2004
DOI: 10.1093/tropej/50.6.364
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency of Nutritional Rickets among Hospitalized Infants and its Relation to Respiratory Diseases

Abstract: This case control study was conducted to determine the frequency of nutritional rickets among hospitalized infants and to assess their relation to respiratory diseases. All infants between the age of 3 months and 2 years admitted to the pediatric ward of Queen Alia Military Hospital during the period February-October 2001 were examined and investigated to rule out nutritional rickets. Children admitted for the first time to hospital for acute illnesses were only included in the study. A special data collection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
97
3
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(107 citation statements)
references
References 0 publications
1
97
3
4
Order By: Relevance
“…It has been demonstrated in the studies conducted that vitamin D deficiency may play a role in the development of autoimmune diseases, inflammatory bowel disease, rheumatoid arthritis, psoriasis, multiple sclerosis, diabetes, certain types of cancer, cardiac failure, stroke, and infectious diseases, such as tuberculosis and pneumonia, and that vitamin D treatment is efficacious in these patients. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] Vitamin D ensures blood pressure regulation by inhibiting RAAS and PTH. 32,33 The studies showed that the levels of renin and angiotensin II could be diminished with vitamin D and its analogues.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated in the studies conducted that vitamin D deficiency may play a role in the development of autoimmune diseases, inflammatory bowel disease, rheumatoid arthritis, psoriasis, multiple sclerosis, diabetes, certain types of cancer, cardiac failure, stroke, and infectious diseases, such as tuberculosis and pneumonia, and that vitamin D treatment is efficacious in these patients. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] Vitamin D ensures blood pressure regulation by inhibiting RAAS and PTH. 32,33 The studies showed that the levels of renin and angiotensin II could be diminished with vitamin D and its analogues.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, vitamin D is known to play a role in the human antimicrobial response (Cannell et al, 2006;Liu et al, 2006) and pulmonary function (Black and Scragg, 2005). Vitamin D deficiency is known to cause rickets and there are a lot of studies showing the correlation between rickets and acute lower respiratory infection (ALRI) in children (Muhe et al, 1997;Najada et al, 2004). However, Wayse et al (2004) were the first to find an association of subclinical 25-hydroxy vitamin D (25(OH)D) deficiency and ALRI in nonrachitic children.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade of twentieth century there was evidence that there is higher incidence of recurrent respiratory tract infection and nutritional rickets [48,49]. The evidence that the peak of viral infection is in the winter time when synthesis of vitamin D across the skin is naturally impaired supported that association.…”
Section: Vitamin D and Asthmamentioning
confidence: 99%
“…The evidence that the peak of viral infection is in the winter time when synthesis of vitamin D across the skin is naturally impaired supported that association. In addition, other studies have proved that vitamin D deficiency in pregnant women may result in increased risk of respiratory tract infections in their infants [44][45][46][47][48][49]. The majority of immune cells express VDRs, mainly after they themselves have been stimulated [40,41,48].…”
Section: Vitamin D and Asthmamentioning
confidence: 99%
See 1 more Smart Citation